Accounting for Vulnerability of African Countries in Performance Based Aid Allocation - Patrick Guillaumont; Sylviane Guillaumont Jeanneney (Fondation pour les études et recherches sur le développement international (FERDI), 2009)
The African Development Bank allocates its concessional resources through a procedure which is mainly based on the quality of the beneficiary countries' economic policy and governance. This allocation procedure relies mainly on the Performance-Based Allocation formula which can be criticized on two grounds. Firstly, the weight on economic policy and governance is viewed as being excessive. Secondly, it lacks transparency and consistency. We consider how to amend that formula so as to take into account certain common characteristics of many African countries. The main proposal is to augment the formula by an economic vulnerability criterion. The numerical simulations show that the introduction of the United Nations economic vulnerability index in the formula gives rise to allocations which not only account for post conflict situations but also inherent fragility. We also consider a lower population weight in order to address the problem of country size. This change helps avoid inconsistencies arising from the application of country allocation ceilings in the various stages of the computation. Finally, a few proposals concerning the African Development Fund's support to regional integration are explored.Ici disponible en tant que document de travail de la Banque africaine de développement.
Keywords: F35; O19; 330